Flexural properties and morphological structures of epoxy composites reinforced with platelet and tubular nanoclays - Dong, Yu; Mathew, Roney; Chaudhary, Deeptangshu; Bickford, Thomas; Haroosh, Hazim (UNSW, 2011)
Epoxy resins offer attractive material merits of low cost, ease of processing, fine adhesion to many substrates and good chemical resistance with a wide range of applications such as adhesives, construction materials and composite laminates. Nanofillers such as carbon nanotubes (CNTs), nanosilica and nanoclays have shown the size effect with a large surface to volume ratio, as opposed to conventional microfillers, which yield less material defects and increase particle/matrix interfacial area if composite properties are well tailored. This paper describes the use of two different shapes of nanoclays (i.e. tubular and platelet-like) to reinforce the epoxy resin with different clay loadings from 1, 3, 5 to 8 wt% via mechanical mixing and ultrasonic treatment. Epoxy composite samples prepared by solution casting underwent flexural tests in three-point bending mode, scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis to correlate the morphological structure, clay dispersion with the resulting felxural properties. It was found that the flexural moduli of epoxy composites were moderately improved by the maximum value of 37% of 8 wt% platelet clay inclusions while a general downside trend of flexural strengths became manifested as compared to that of neat epoxy. As expected, microsized clay agglomerates in an undispersed form deteriorate the functionalised mecnaical performance of such epoxy composite system.